Effect of Quaternary Ammonium Salt on Shear Bond Strength of Orthodontic Brackets to Enamel - Ghadirian, Hannaneh (J Dent (Tehran), 2017)
OBJECTIVES: This study sought to assess the effect of quaternary ammonium salt (QAS) on shear bond strength of orthodontic brackets to enamel. MATERIALS AND METHODS: In this in vitro experimental study, 0, 10, 20 and 30% concentrations of QAS were added to Transbond XT primer. Brackets were bonded to 60 premolar teeth using the afore-mentioned adhesive mixtures, and the shear bond strength of the four groups (n=15) was measured using a universal testing machine. After debonding, the adhesive remnant index (ARI) score was determined under a stereomicroscope. Data were analyzed using one-way ANOVA. RESULTS: The mean and standard deviation of shear bond strength of the control and 10%, 20% and 30% groups were 23.54±6.31, 21.81±2.82, 20.83±8.35 and 22.91±5.66 MPa, respectively. No significant difference was noted in shear bond strength of the groups (P=0.83). Study groups were not different in terms of ARI scores (P=0.80). CONCLUSIONS: The results showed that addition of QAS to Transbond XT primer had no adverse effect on shear bond strength of orthodontic brackets.